EARLY STROKE PREVENTION BY IMPROVING THE ROLE OF TEACHERS AND STUDENTS - Tunik, Tunik; Yulidaningsih, Elok; M, Yuyun Putri (SYNTIFIC, 2024)
Background. Stroke is a disease of acute decreased nerve function caused by sudden disruption of the brain's blood vessels. Some efforts to prevent strokes need to be carried out at an early age by controlling risk factors for stroke, particularly stroke risk factors in high school adolescents. According to a local survey, almost 90% of teenagers or students of SMK 1 in the 2nd grade have smoking habits, and the number of teenagers who like fast food that is high in carbohydrates, high in fat, high in cholesterol, and do not do any physical exercises regularly. This empowerment aimed to increase the knowledge and skills of teachers and students regarding early stroke prevention. Implementation Method. The Community Service was conducted in 2023. These empowerment methods used public education, counseling, workshops, and practicum. Partners in this empowerment were the teachers and students of SMKN 1 Suruh, Trenggalek, East Java, with 40 students and 6 teachers. Findings. This study showed the increased knowledge of teachers and students about stroke risk factors and early stroke prevention, as well as increased skills in measuring blood pressure. There were 50% of students had sufficient knowledge about stroke risk factors, 50% had adequate skills in measuring BP, and 92.5% of students had a smoking history. Conclusion. In conclusion, knowledge about stroke risk factors and early prevention of stroke must be carried out starting from an early age, because stroke strikes anyone and varied ages.